Soc. Alexander Rodrigues LTD.: When minority holds the power - Menéres, Pedro Bravo (2019)
This case presents a real decision set regarding the future of a family business reaching its 6th generation, whose high dispersion of shares and estrangement between family branches yielded a risky deadlock for the business growth and survival. Written from the family CEO’s perspective, the case depicts his need to attract the passive and dissenting wings of shareholders, after running through the whole history of relational problems between them. At stake is a nonconsensual diversifying investment opportunity, which is key to the survival and growth of the business, yet is dependent on a hardly attainable qualified majority voting.